2019
DOI: 10.5194/esurf-7-1041-2019
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the disequilibrium in denudation rates due to divide migration at the scale of river basins

Abstract: Abstract. Basin-averaged denudation rates may locally exhibit a wide dispersion, even in areas where the topographic steady state is supposedly achieved regionally. This dispersion is often attributed to the accuracy of the data or to some degree of natural variability of local erosion rates which can be related to stochastic processes such as landsliding. Another physical explanation of this dispersion is local and transient disequilibrium between tectonic forcing and erosion at the scale of catchments. Recen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In the Rotating and Spheres models, we also observed that maximum divide orders occasionally extend to higher values, but these changes are rather small. We note that the above observations also prevail when considering divide distance instead of divide order because the two are linearly related (Scherler and Schwanghart, 2020a), with divide distance ∼ 430 m × divide order. The 430 m corresponds to the mean length of the divide segments.…”
Section: Network Topologymentioning
confidence: 73%
See 4 more Smart Citations
“…In the Rotating and Spheres models, we also observed that maximum divide orders occasionally extend to higher values, but these changes are rather small. We note that the above observations also prevail when considering divide distance instead of divide order because the two are linearly related (Scherler and Schwanghart, 2020a), with divide distance ∼ 430 m × divide order. The 430 m corresponds to the mean length of the divide segments.…”
Section: Network Topologymentioning
confidence: 73%
“…For each modeled topography and at each time step (dt = 40 000 years), we first computed flow directions and flow accumulation, and we subsequently identified the stream network using a drainage area threshold of 0.2 km 2 . We next derived the drainage divide network on the basis of the stream network and using the algorithm proposed in Scherler and Schwanghart (2020a). We calculated divide distances and divide orders based on the Topo ordering scheme (Scherler and Schwanghart, 2020a).…”
Section: Topographic Analysismentioning
confidence: 99%
See 3 more Smart Citations